Maintaining Family Communication in Long-Distance Relationship Between International Students and Parents - Kania Salsabila Putri Rachmadi; Turnomo Rahardjo; Amida Yusriana (Interaksi Online, 2023)
Communication is an important thing in an individual's life. Communication is also necessary for the family environment to maintain a harmonious relationship among family members. Parents certainly want the best for their children, including children's education, and they are willing to let their children study abroad, which makes them have to undergo long-distance relationships. In long-distance relationships, parents and children will face difficulties and challenges that require them to maintain family communication, including self-disclosure and trust in each other. The theory used in this research is the Self-Disclosure Theory by Altman and Taylor (1973). This study uses a qualitative interpretive research method with a phenomenological approach focusing on the informants' experiences. In addition, the researcher used in-depth interview techniques in the data collection process to gather information about the experience of parents and children on how they maintain family communication in long-distance relationships. Based on the research conducted on children studying abroad and parents experiencing long-distance relationships, it was found that each family has different ways of maintaining family communication during long-distance relationships. Maintaining family communication in long-distance relationships requires self-disclosure and a sense of trust in each other to achieve a harmonious family relationship. In this study, parents and children are committed to maintaining family communication so that family communication can remain stable and effective as before in a long-distance relationship. Overall, results suggested that a person’s commitment to the relationship is enhanced by their maintenance efforts to maintain family communication in a long-distance relationship.